2020
DOI: 10.1021/acs.jpcb.0c05347
|View full text |Cite
|
Sign up to set email alerts
|

Implicit Modeling of the Impact of Adsorption on Solid Surfaces for Protein Mechanics and Activity with a Coarse-Grained Representation

Abstract: Surface immobilized enzymes play a key role in numerous biotechnological applications such as biosensors, biofuel cells or biocatalytic synthesis. As a consequence, the impact of adsorption on the enzyme structure, dynamics and function needs to be understood on the molecular level as it is critical for the improvement of these technologies. With this perspective in mind, we used a theoretical approach for investigating local protein flexibility on the residue scale that couples a simplified protein representa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…16 This can be achieved either through targeted chemical linkage between the protein and the surface, [17][18][19] or via the adequate functionalization of the surface, for exemple with self-assembled monolayer (SAMs), in order to adapt its charge and physico-chemical properties to a specific protein. [20][21][22][23] One must also pay attention to the conservation of the adsorbed protein's structure and dynamics, as perturbations in the protein conformation [24][25][26] or internal mobility 27 are likely to result in a dramatic decrease of the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…16 This can be achieved either through targeted chemical linkage between the protein and the surface, [17][18][19] or via the adequate functionalization of the surface, for exemple with self-assembled monolayer (SAMs), in order to adapt its charge and physico-chemical properties to a specific protein. [20][21][22][23] One must also pay attention to the conservation of the adsorbed protein's structure and dynamics, as perturbations in the protein conformation [24][25][26] or internal mobility 27 are likely to result in a dramatic decrease of the catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopy coupled to electrochemistry will allow the mapping of the electrocatalysis [318][319][320]. Finally, getting more and more accurate experimental data on enzyme behavior on electrodes may be implemented in theoretical models that in return will help in bioelectrode rationalization [21,117,[321][322][323].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of immobilized enzyme, it was expected that only the amino acids on the surface of the enzyme will sense the support. However, by looking at the rigidity profile obtained by Brownian dynamics simulations, it was very recently shown that even amino acids in the core of the enzyme can be affected depending on the surface charge of the support [117].…”
Section: Enzyme Orientation On the Surfacementioning
confidence: 99%
“…In this view, specific surface topographies and surface modifiers would determine protein coronas with selected compositions [ 147 ]. Regarding protein orientation and structural evolution upon corona formation, Bourassin and colleagues proposed a coarse-grained, elastic network representation to implicitly model the impact of surface adsorption on protein mechanics [ 148 ]. However, to obtain design rules for proteins and surfaces with determined binding characteristics, researchers often oversimplify the interaction mechanisms, focusing on only one or a few of the properties influencing the affinity or the specificity of the proteins for the surfaces.…”
Section: Discussionmentioning
confidence: 99%